Diet of Northern Gannet Morus bassanus chicks in North Norway - Barrett, Rob T. (Ornis Norvegica, 2016)
Northern Gannets Morus bassanus established colonies in North Norway in the 1960s, since when the breeding population has increased and spread north- and eastwards. Diet data collected at several colonies in North Norway confirm the Gannet’s opportunistic foraging behaviour with Atlantic herring Clupea harengus, Atlantic mackerel Scomber scombrus, sandeels Ammodytidae and saithe Pollachius virens being the main prey brought to chicks. As such, climate change is unlikely to have a negative effect on the Gannet population in the region.